P106 Validity of the Clinical COPD Questionaire (CCQ) in Non-COPD Patients. (19th November 2012) - Mittal, MM; Kon, SSC; Clark, AL; Dilaver, D; Peasey, MM; Canavan, JL; Jones, SE; Ng, MGS; Polkey, MI; Man, WD-C
Abstract : Background: The Clinical COPD Questionnaire (CCQ) is a 10-item health status instrument that takes only two minutes to complete, and has been shown to be reliable and valid in patients with COPD (van der Molen T et al 2003, Damato S et al 2005). In COPD patients, the CCQ correlates with established health status instruments such as the Chronic Respiratory Disease Questionnaire (CRQ), COPD Assessment Test (CAT) and St George's Respiratory Questionnaire (SGRQ) (Tsiligianni IG et al 2012). Although the CRQ and SGRQ were originally developed in patients with chronic airway obstruction, they are commonly used in clinical practise in chronic respiratory diseases other than COPD. We hypothesised that the CCQ would correlate with existing health status measures and exercise capacity in a survey of non-COPD patients Methods: 60 patients were recruited from respiratory outpatient clinics. Disease classifications included interstitial lung disease (n=23), asthma (n=10), bronchiectasis (n=17), extrathoracic restriction (n=8) and thoracic surgery for lung cancer (n=2). CCQ, CAT, CRQ, SGRQ and incremental shuttle walk (ISW) were recorded. Spearman's rank correlation was used to assess the relationship between CCQ and other outcome measures. Results: Baseline characteristics are presented as mean (standard deviation) or median (25th, 75th percentiles); Age 65 (58, 77), FEV1% predicted 69.8 (24.4), BMI 28.0 (25.4, 32.3), MRC 3(1), CCQ 2.1 (1.5, 3.8) and ISW 210 (90, 320). There was a significant correlation between the total CCQ and CAT, SGRQ, CRDQ, MRC and ISW (all p<0.01 see Table. 1 ). In addition individual domains of the CCQ correlated significantly with MRC, CAT and individual domains of the CRQ (p<0.01). Conclusions: The CCQ correlates well with existing health status and functional outcome measures in non-COPD patients. CCQ may be a useful assessment tool to test the efficacy of interventions such as pulmonary rehabilitation in this population, but longitudinal studies are required to confirm.